Association of easy albumin-bilirubin score with increased mortality in adult trauma patients - Hsu, Shiun-Yuan; Rau, Cheng-Shyuan; Tsai, Ching-Hua; Chou, Sheng-En; Su, Wei-Ti; Hsieh, Ching-Hua (Frontiers in Surgery, 2024)
The easy albumin-bilirubin (EZ‐ALBI) score is calculated using the equation: total bilirubin (mg/dL) - 9 × albumin (g/dL), and is used to evaluate liver functional reserve. This study was designed to investigate whether the EZ-ALBI score serves as an independent risk factor for mortality and is useful for stratifying the mortality risk in adult trauma patients. We retrospectively reviewed data from the registered trauma database of the hospital and included 3,637 adult trauma patients (1,241 deaths and 2,396 survivors) due to all trauma caused between January 1, 2009, and December 31, 2021. The patients were allocated to the two study groups based on the best EZ-ALBI cutoff point (EZ-ALBI = -28.5), which was determined based on the area under the receiver operating characteristic curve. Results revealed that the non-survivors had a significantly higher EZ-ALBI score than the survivors (-26.4 ± 6.5 vs. -31.5 ± 6.2, p < 0.001). Multivariate logistic regression analysis revealed that EZ-ALBI ≥-28.5was an independent risk factor for mortality (odds ratio, 2.31; 95% confidence interval, 1.63–3.28; p < 0.001). Patients with an EZ-ALBI score ≥-28.5 presented with 2.47-fold higher adjusted mortality rates than patients with an EZ-ALBI score <-28.5. A propensity score-matched pair cohort of 1,236 patients was developed to reduce baseline disparities in trauma mechanisms. The analysis showed that patients with an EZ-ALBI score ≥-28.5 had a 4.12 times higher mortality rate compared to patients with an EZ-ALBI score <-28.5. The EZ-ALBI score was a significant independent risk factor for mortality and can serve as a valuable tool for stratifying mortality risk in adult trauma patients by all trauma causes.